Improvement of gelation properties of myofibrillar proteins from porcine longissimus dorsi muscle through microwave combined with air convection thawing treatment - Han, Fenxia; Zhu, Mingming; Xing, Yi; Ma, Hanjun (International Journal of Agricultural and Biological Engineering, 2023)
The effects of the microwave combined with air convection thawing (MAT) on the gelling properties of pork myofibrillar proteins (MPs) were further studied and compared with those of fresh meat (FM), and single thawing methods (microwave thawing (MT) and air convection thawing (AT)). Results revealed that the thawing methods, excluding MAT, induced deterioration in the gelling properties of MPs. There was no significant difference (p>0.05) in the water holding capacity (WHC), cooking loss, whiteness, and strength of gel samples subjected to MAT and those of FM samples, demonstrating that the gelling properties were retained after MAT. As well, protein aggregation was limited, since MAT reduced the change in zeta potential and turbidity compared to that observed with MT or AT. The dynamic rheology and scanning electron microscopic results were relatively consistent, revealing that among the different thawing techniques, MAT had the least negative impact on the microstructure of MPs gel, leading to the generation of a more elastic and uniform gel structure than that of the MT or AT gels. Moreover, MAT resulted in higher water retention in the gels than that achieved with MT or AT. These findings indicated that MAT improved the gelling properties of MPs, thereby confirming the suitability of this treatment for use in the meat processing industry.Keywords: microwave combined with air convection thawing, gelling property, myofibrillar protein, moisture distribution, microstructureDOI: 10.25165/j.ijabe.20231603.7842Citation: Han F X, Zhu M M, Xing Y, Ma H J. Improvement of gelation properties of myofibrillar proteins from porcine Longissimus dorsi muscle through microwave combined with air convection thawing treatment. Int J Agric & Biol Eng, 2023; 16(3): 254–261.